Differentials in sexual and reproductive health knowledge among East Malaysian adolescents - Halimah, Binti Awang; Wah, Yun Low; Wen, Ting Tong; Lih, Yoong Tan; Cheah, Whye Lian; Helen Benedict, Lasimbang; Hamizah, Binti Mohd Hassan (Cambridge University Press, 2018)
The aim of this study was to assess the knowledge of East Malaysian adolescents on sexual and reproductive health issues. Data were collected in March–July 2015 from 2858 adolescents aged 13–18 years from selected East Malaysian secondary schools using a self-administered questionnaire. Twelve items relating to sexual and reproductive health were used to measure respondents’ knowledge based on their responses ‘True’, ‘False’ or ‘Don’t know’, with the proportion of correct answers being the variable of interest. Cronbach’s alpha for the twelve items was 0.761 and the mean knowledge score was 6.8. While the majority of the respondents knew that a woman can get pregnant if she has sex with a man and that HIV and AIDS can be transmitted through sexual intercourse, knowledge about Malaysia’s abortion laws, that a woman can get pregnant if she has sex only once and that people with sexually transmitted infections may look healthy was poor. Older respondents and those from urban schools reported significantly higher knowledge than younger respondents and those from rural schools, respectively. More emphasis should be given in schools to the specific topics for which low levels of sexual and reproductive health knowledge were found, with greater attention being given to younger adolescents and those in rural areas.